CAPABILITY FAILURES AND CORROSIVE DISADVANTAGE IN A VIOLENT RAINFOREST METROPOLIS. Issue 1 (1st January 2023) - PIVA da SILVA, MARIANA; Fraser, James Angus; Parry, Luke
Abstract: Governments continue to narrowly equate improved well-being with economic growth, contrary to decades of development scholarship. The capabilities approach, instead, emphasizes freedom and what individuals are able to do and to be within society. However, it underplays structural determinants of social inequities and says little about violence, a dominant problem in metropolitan areas of Latin America. Framing our analysis around capabilities and theorizing on disadvantage, we examine experiences of inequity and violence in Manaus, a metropolis in the Brazilian Amazon. We show how the threat of physical violence is highly corrosive because it underpins a cluster of disadvantage that profoundly impacts central capabilities, including emotions, bodily integrity, and affiliation. Social isolation is commonplace because interactions are perceived as risks rather than pathways to mutual recognition. Violence begets violence in low-income neighborhoods and this constrains capabilities, causes shame and indignity, and limits potential for self-realization. Policy makers should address how disadvantaged people feel about themselves, relate to others, and are able to decide how to conduct their daily lives.